To solve the equation using inverse operations, we want to isolate the variable, which in this case is "c".
First, we can add 1/4 to both sides of the equation to get:
c - 1/4 + 1/4 = 2 + 1/4
This simplifies to:
c = 2 + 1/4
To add 2 and 1/4, we need to have a common denominator. The common denominator of 4 and 1 is 4. We can rewrite 2 as 8/4 to have a common denominator:
c = 8/4 + 1/4
Now, we can add the fractions:
c = (8 + 1) / 4
This simplifies to:
c = 9/4
Therefore, the solution is c = 9/4.
The answer is not one of the options given.
Solve using inverse operations.
c-1/4=2
A
2 142\ \frac{1}{4}2
4
1
B
34\frac{3}{4}
4
3
C
1 341\ \frac{3}{4}1
4
3
D
−2 14-2\ \frac{1}{4}−2
4
1
5 answers
just pick one that closes
In that case, we can choose option D) -2 1/4
Solve using inverse operations.
v+11/3=1/3
A
103\frac{10}{3}
3
10
B
-4
C
−103-\frac{10}{3}−
3
10
D
4
v+11/3=1/3
A
103\frac{10}{3}
3
10
B
-4
C
−103-\frac{10}{3}−
3
10
D
4
To solve the equation using inverse operations, we want to isolate the variable "v".
First, we need to eliminate the 11/3 on the left side of the equation by subtracting 11/3 from both sides:
v + 11/3 - 11/3 = 1/3 - 11/3
This simplifies to:
v = 1/3 - 11/3
Next, we need to subtract the fractions. To do this, we find a common denominator, which is 3:
v = (1 - 11)/3
Simplifying the numerator, we have:
v = -10/3
Therefore, the solution is v = -10/3.
The correct answer is C) -10/3.
First, we need to eliminate the 11/3 on the left side of the equation by subtracting 11/3 from both sides:
v + 11/3 - 11/3 = 1/3 - 11/3
This simplifies to:
v = 1/3 - 11/3
Next, we need to subtract the fractions. To do this, we find a common denominator, which is 3:
v = (1 - 11)/3
Simplifying the numerator, we have:
v = -10/3
Therefore, the solution is v = -10/3.
The correct answer is C) -10/3.